Factors Related to the Willingness of People with Mental Health Illnesses Living in Group Homes to Disclose Their Illness to Supporters during Disaster Evacuation: A Cross-Sectional Study - Masato Oe; Hisao Nakai; Yutaka Nagayama (MDPI AG, 2024)
Severe heavy rains caused by linear precipitation systems are occurring more frequently in Japan owing to climate change, and residents are being asked to evacuate more often. The purpose of this study was to identify factors associated with the willingness of people with mental health illness (PMHI) in group homes to disclose their illness when being evacuated. Participants were PMHI living in group homes in Japan. We conducted an original anonymous self-administered questionnaire based on previous research. Valid data from 119 people were analyzed. Factors associated with the willingness to disclose illness to supporters upon evacuation were "I can imagine living in a public shelter" (Odds Ratio [OR] 4.50, 95% Confidence Interval [CI]: 1.78-11.43), and "I socialize with neighbors" (OR 5.63, 95% CI: 1.74-18.22). Managers of group homes should encourage PMHI to imagine life in an evacuation zone by increasing opportunities for disaster training and for interaction with local residents. People who are less likely to socialize with neighbors should be especially careful, as they may not be able to disclose their illness, and those who support evacuees should pay special attention to these people.